Grief and Self-Healing Due to the Death of a Parent - Angela, Shelfia; Kabri, Kabri; Nyanasuryanadi, Partono (Journal of Education Technology Information Social Sciences and Health, 2025)
The concept of "death" brings to mind the profound anxiety associated with the irreversible absence of significant individuals, including parents, family members, friends, and partners. The passing of a parent can trigger intense feelings of sorrow that deeply affect the children who remain. This research employs the Systematic Literature Review (SLR) methodology to scrutinise existing pertinent studies regarding grief and self-healing following the loss of a parent. A meta-synthesis was performed to address the research inquiry concerning grief and self-healing in the context of parental death. The aim of this SLR investigation is to enhance the understanding of grief and self-healing resulting from the death of a parent; to enrich comprehension through a literature review of ten carefully selected studies; to conduct an in-depth examination of the research and the depth of discussion; and to provide substantiation for grief and self-healing associated with the loss of a parent. A systematic review was conducted following the PRISMA framework, analysing articles published from 2020 to 2024 on the topic of grief and self-healing after the loss of a parent. Research articles were sourced using keywords like "grief," "self-healing," "bereavement," "resilience," and "parental death" in the Google Scholar database. Mendeley was used to manage titles and abstracts, eliminating duplicate entries. The study utilized the meta-synthesis method for a qualitative systematic review, focusing on ten relevant journals. The research process involved defining the problem, conducting a thorough literature search, and analysing the selected studies in detail. Data collection involved reviewing previous studies to draw conclusions, with a focus on different research methodologies related to death and self-healing post-parental loss. The selected articles, available in English and Indonesian, were analysed using the VOSviewer application, revealing common keywords such as "Resilience," "Loss," "Grief," "Self-healing," and "Death."